Designing Restorative City Models for Child Safety and Crime Prevention: Insights from the Global South - Csongor, Herke; Barbara Katalin, Herke-Fábos; Bushrat, Jahan (Urban Planning and Construction, 2025)
This study explores restorative city models as holistic approaches to urban safety and child protection, particularly within the Global South. By integrating restorative justice, inclusive urban design, child rights, and community participation, restorative cities aim to address the root causes of crime and social disintegration. Utilizing a qualitative comparative case study approach, the research analyzes initiatives in cities including Hull, Leuven, Medellín, and Nairobi. Key findings reveal that interventions such as school-based mediation, child-friendly infrastructure, and trauma-informed planning significantly reduce youth violence and foster community trust. While challenges such as institutional resistance and resource limitations persist, case evidence suggests that restorative frameworks are adaptable across diverse socio-economic contexts. The study concludes with a policy-oriented roadmap advocating for participatory planning, inter-sectoral coordination, and capacity-building as key strategies for implementing restorative urban models. In doing so, it positions restorative cities as practical solutions for advancing child welfare, community resilience, and long-term urban peace. Beyond these core findings, the research underscores the versatility of restorative approaches in addressing both crimes committed against children and those committed by them. The comparative analysis reveals that, when tailored to local socio-cultural contexts, restorative city models can generate measurable reductions in violence, enhance institutional trust, and foster inclusive civic participation, making them an essential policy direction for sustainable urban development in both resource-rich and resource-constrained settings.